A Sensor Array for the Measurement of Relative Motion in Lower Limb Prosthetic Sockets - Veronika Noll; Sigrid Whitmore; Philipp Beckerle; Stephan Rinderknecht (Sensors, 2019)
The relative motion between residual limb and prosthetic socket could be a relevant factor in quantifying socket fit. The measurement of these movements, particularly in dynamic gait situations, poses a challenging task. This paper presents the realization of a measurement concept based on multiple optical 2D-motion sensors. The performance of the system was evaluated on a test rig considering accuracy and precision as well as accomplished measurement frequency and reliability of the system. Additionally, results of a pilot study measuring the relative motion between residual limb and prosthetic socket at seven specific locations of one individual with transtibial amputation during straight level walking are presented. The sensor functionality of the array was confirmed and the test rig experiments were comparable to the previously tested functional model ( <semantics> e r r rel = 0.52 ± 1.87 </semantics> %). With a sampling frequency of 1.3 kHz to be distributed among the number of sensor units, the developed system is suitable for investigating the relative movement between residual limb and prosthetic socket in dynamic gait situations. Results of the pilot study show the majority of relative motion occurring during the second half of the gait cycle. The measured relative motions show the residual limb sinking deeper into the socket, extending in the Sagittal plane and rotating internally in the Transverse plane during stance phase. Data captured during swing phase indicate a lower limb extension in the Sagittal plane as well as an external rotation in the Transverse plane.